REVOLUTIONIZING SELF-COMPACTING CONCRETE BY EXPLORING STRENGTH AND PERFORMANCE - Vikas, B.S Walia (Chelonian Research Foundation, 2025)
In recent years, self-compacting concrete (SCC) has gained significant attention in the construction industry due to its excellent workability, durability, and potential for enhanced structural performance. This study investigates the strength and performance characteristics of an M25 mix design of SCC, exploring various material replacements to optimize its compressive strength. The research specifically analyzes the compressive strength of three design categories: an M25 mix design without any material replacement, an M25 mix design with a 16% replacement of Alccofine, and an M25 mix design incorporating both 16% Alccofine and varying percentages of porcelain aggregates (1%, 2%, 3%, 4%, and 5%). The findings reveal that the M25 mix with 16% Alccofine achieves a noteworthy compressive strength, surpassing the traditional mix design. Moreover, introducing porcelain aggregates alongside Alccofine reveals a synergistic effect, particularly at a 16% Alccofine and 3% porcelain replacement, which exhibits the highest compressive strength compared to other combinations. The optimization of these materials not only enhances the mechanical properties but also contributes to sustainability by utilizing industrial by-products, such as Alccofine and porcelain waste, in concrete production. This research highlights the viability of using alternatives to traditional materials in SCC formulations, emphasizing the potential for innovative mix designs in enhancing concrete performance. The outcomes underscore the importance of exploring synergy between different materials to achieve superior mechanical properties, safeguarding structural integrity while promoting eco-friendly practices in the construction domain.